Inorganic synthesis inside carbon nanotubes - Stoppiello, Craig Thomas (2017)
The use of single-walled carbon nanotubes (SWNTs) as test tubes for the encapsulation of metallic nanoparticles (MNPs) and the formation of inorganic nanomaterials has been advanced. A methodology to encapsulate the group 10 and 11 metals inside SWNTs to investigate their properties has been optimised. Each metal interacts with carbon differently at the atomic level, as shown by aberration-corrected high resolution transmission electron microscopy (AC-HRTEM), leading to the promotion of a plethora of different processes stimulated by MNPs under the electron beam. Additionally, interactions between SWNTs and small clusters of the group 10 metals have been examined, revealing marked differences between metal-carbon bonding for each metal. This has allowed for a useful insight into metal-carbon interactions on the atomic level which could have profound implications on the future development of new catalysts or nanoscale devices. Following on from this, a series of chemical reactions with platinum compounds were carried out within SWNTs which have shown SWNTs to be both a very effective reaction vessel and template for the formation of low-dimensional PtX2 (X = I, S) nanocrystals, materials that are difficult to create by traditional synthetic methods. The stepwise synthesis within SWNTs has enabled the formation of the platinum compounds to be monitored at each reaction stage by AC-HRTEM, verifying the atomic structures of the products and intermediates, and also by an innovative combination of fluorescence-detected X-ray absorption spectroscopy (FD-XAS) and Raman spectroscopy, monitoring the oxidation states of the platinum guest compounds within the nanotube and the vibrational properties of the host SWNT respectively. The stepwise synthesis has appeared to offer only limited preparative potential because of the lack of stoichiometric control in the resultant inorganic nanomaterials. A new approach for nanoscale synthesis in nanotubes developed in this study utilises the versatile coordination chemistry of platinum which has enabled the insertion of the required chemical elements (e.g. metal, and halogens or chalcogens) into the nanoreactor in the correct proportions for the controlled formation of PtI¬2 and PtS2 with the exact stoichiometry and structure. FD-XAS has also been used to probe the transformations of Pt(acac)2@SWNT to Pt@SWNT, and Cu(acac)2@SWNT to Cu2Ox@SWNT (where x > 1). It was shown that the temperature of both transformations was significantly lower than required for the same reactions in the bulk, which demonstrates the ability of SWNTs to lower the activation energy by polarising encapsulated molecules. Finally, a variety of novel MNPs and MO¬x¬ (M = Pt, Pd, Ni) materials were encapsulated within hollow graphitised carbon nanofibres (GNFs) and evaluated for the sensing of glucose. MOx@GNFs were revealed to be more active sensors than their corresponding MNPs which can be attributed to the increase in Lewis acidity of the metal centres upon oxide formation. Furthermore, the effectiveness of each metal and their corresponding oxides for glucose detection was found to increase in the order Pt > Pd > Ni which can be attributed to both physical and chemical properties of the respective metals. Overall, this thesis demonstrates that nanotubes can be used effectively to not only investigate chemical transformations on the atomic level, but also act as nano-sized test tubes and templates for the formation of novel, low-dimensional inorganic materials with bespoke structure and composition.